2n-5 = 8n+7 Subtract 8n from both sides and add 5 to both sides:- -6n = 12 Divide both sides by -6 to find the value of n:- n = -2
3+3 is 6
The GCF is 6.
x(x2+5x+6)
2(x+3)
Yes. First you need to factor out a 3 so the equation becomes 3(n2-8n+12). Then you need to factor what's in the parenthesis, which would be (n-6)(n-2). So, the answer is 3(n-6)(n-2).
2(n2+3n-54) 2(n+9)(n-6)
It is an expression that can be simplified to -4n-1
n = 1/2
n = -6
n2 + 9n + 18 = (n + 6)(n + 3)
n = 1/2
2n-5 = 8n+7 Subtract 8n from both sides and add 5 to both sides:- -6n = 12 Divide both sides by -6 to find the value of n:- n = -2
This can not be solved as it is not an equation but a simple expression. If you are looking to factor it, then the answer is: n2 - 3n - 18 = (n - 6)(n + 3)
yes because the + and the - are two terms. hope this helps :3
6 is a factor
The balanced equation for the reaction of hydrogen gas (H2) with nitrogen gas (N2) to form ammonia (NH3) is: 3H2 + N2 → 2NH3